2018
DOI: 10.1177/0023830918803978
|View full text |Cite
|
Sign up to set email alerts
|

Imitation in a Second Language Relies on Phonological Categories but Does Not Reflect the Productive Usage of Difficult Sound Contrasts

Abstract: This study investigated the relationship between imitation and both the perception and production abilities of second language (L2) learners for two non-native contrasts differing in their expected degree of difficulty. German learners of English were tested on perceptual categorization, imitation and a word reading task for the difficult English /ɛ/-/æ/ contrast, which tends not to be well encoded in the learners’ phonological inventories, and the easy, near-native /i/-/ɪ/ contrast. As expected, within-task c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 77 publications
(146 reference statements)
2
44
0
Order By: Relevance
“…A two-alternative forced-choice task (2AFC) assessed the learners' phonetic categorization of the /ε/-/ae/ contrast. The task used here was the same as the one described in Llompart and Reinisch (2019a). A 21-step bet-bat continuum was created in Praat (Boersma & Weenink, 2010) from natural productions from the same speaker who recorded the words for the lexical decision task.…”
Section: Phonetic Categorization Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…A two-alternative forced-choice task (2AFC) assessed the learners' phonetic categorization of the /ε/-/ae/ contrast. The task used here was the same as the one described in Llompart and Reinisch (2019a). A 21-step bet-bat continuum was created in Praat (Boersma & Weenink, 2010) from natural productions from the same speaker who recorded the words for the lexical decision task.…”
Section: Phonetic Categorization Taskmentioning
confidence: 99%
“…Performance in the phonetic categorization task was measured by calculating the steepness (i.e., slope) of the /ε/-/ae/ categorization curve. Following Llompart and Reinisch (2019a), individual slopes were calculated by submitting the categorization data to a generalized linear mixed-effects regression model with a logistic linking function (lme4 package 1.1-20, Bates, Mächler, Bolker & Walker, 2015) in R (Version 3. 5.…”
Section: Categorization and Vocabulary: Obtaining Individual Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…They tested how well German learners can comprehend German-accented English, with the crucial manipulation whether learners were listening to their own voice or someone else's English. This was tested with minimal word pairs containing phonological contrasts that are typically close to neutralized in German-accented English [7,8,9,10]. [7] showed that most German learners did not produce the contrast as native speakers do, however, they did not neutralize it either.…”
Section: Introductionmentioning
confidence: 99%
“…However, no overall differences could be found between the two groups for either the use of the familiar cue of vowel duration or the 'unfamiliar' cue of glottalization. Note, however, that although such group-level differences are typically easier to detect than correlations at the individual learner level (e.g., Llompart & Reinisch, in press), ratings from language background questionnaires rarely predict effects in phonetic tasks-likely due to the overall good performance and relatively small variability in phonetic tasks (compared to lexical tasks; Eger & Reinisch, 2017;Llompart & Reinisch, 2019).…”
Section: Discussionmentioning
confidence: 99%